Plant growth-promoting bacteria effect in withstanding drought in wheat cultivars - Furlan, Fernando; Saatkamp, Kléber; Gazolla Volpiano, Camila; de Assis Franco, Francisco; Fonseca dos Santos, Marise; Gruszka Vendruscolo, Eliane Cristina; Guimarães, Vandeir Francisco; Torres da Costa, Antonio Carlos (Scientia Agraria, 2017)
Plant growth-promoting bacteria (PGPB) have been used as biofertilizer. However, considering the specificity of the plant-bacteria interaction, the effect of PGPB inoculation in wheat under water stress is still poorly understood. The aim of this work was to evaluate wheat genotypes under water shortage inoculated with Azospirillum brasilense and Herbaspirillum seropedicae, with and without nitrogen fertilization. Therefore, samples for relative water content (RWC) and membrane stability index (MSI) evaluations were collected at the 1st and 8th days of a total water restriction at booting stage. In addition, biomass, total nitrogen (TN) and yield parameters were determined at the harvesting. As results, genotypes showed a distinct performance. RWC and MSI data revealed that A. brasilense and H. seropedicae inoculation are able to lead CD 120 to drought tolerance. In addition, grain index was improved in all conditions where H. seropedicae was present under both different water regimes. H. seropedicae with nitrogen fertilizer also increased grain yield under water shortage regime. Furthermore, A. brasilense with nitrogen fertilizer was also able to improve 1000-grain mass of plants under water shortage. Frontana exhibited the maintenance of cellular integrity and RWC only when H. seropedicae and with both bacteria plus nitrogen were applied, however this cultivar did not present differences in terms of biomass, TN or productivity. These results pointed out H. seropedicae as promising to inoculation in cereals and CD120 as a good plant model to study plant-bacteria interaction.